2017
DOI: 10.3892/ol.2017.5941
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of STMN1 enhances osteosarcoma cell chemosensitivity through inhibition of autophagy

Abstract: Chemoresistance is a major cause for the poor prognosis of osteosarcoma (OS) patients. However, our understanding of mechanisms underlying chemoresistance in OS are limited. The present study aimed to investigate the effect of stathmin 1 (STMN1) on paclitaxel-induced chemoresistance, as well as the underlying mechanism. Western blot analysis data revealed that the expression level of STMN1 was dramatically increased in OS cell lines (HOS, Saos-2, U-2OS and MG-63), when compared to normal osteoblast hFOB1.19 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Jiang et al (41) reported that the inhibition of STMN1 expression using small interfering RNA induced growth inhibition, cell cycle arrest and apoptosis. Other researchers have reported that STMN1 may be involved in the drug resistance of osteosarcoma, and inhibition of STMN1 enhanced the chemosensitivity of osteosarcoma cells (42)(43)(44). In the present study, pMSCV-STMN1 reversed miR-193b-induced inhibition of migration and invasion in F5M2 cells, indicating that miR-193b may inhibit migration and invasion of osteosarcoma through STMN1.…”
Section: Discussionsupporting
confidence: 68%
“…Jiang et al (41) reported that the inhibition of STMN1 expression using small interfering RNA induced growth inhibition, cell cycle arrest and apoptosis. Other researchers have reported that STMN1 may be involved in the drug resistance of osteosarcoma, and inhibition of STMN1 enhanced the chemosensitivity of osteosarcoma cells (42)(43)(44). In the present study, pMSCV-STMN1 reversed miR-193b-induced inhibition of migration and invasion in F5M2 cells, indicating that miR-193b may inhibit migration and invasion of osteosarcoma through STMN1.…”
Section: Discussionsupporting
confidence: 68%
“…The oncogenic role of STMN1 has been previously demonstrated in several types of cancer or in cancer cell lines [ 25 ]. In osteosarcoma cells, knockdown of the STMN1 gene was previously shown to enhance chemosensitivity of osteosarcoma cells to paclitaxel through inhibition of autophagy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on the role of STMN1 in human osteosarcoma are lacking, a recently published in vitro study of human osteosarcoma cell lines showed that knockdown of the STMN1 gene enhanced osteosarcoma cell chemosensitivity by inhibiting autophagy, indicating that STMN1 might be a potential target for the treatment of chemoresistance in osteosarcoma [ 13 ]. However, the clinical significance of STMN1 expression in human osteosarcoma in vivo remains to be elucidated, and the underlying molecular mechanisms for the effects of STMN1 are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma cells invade skin tissue and enter blood vessels, forming metastases at distant sites [ 2 ]. In addition, we have found that STMN1, a cytosolic phosphoprotein [ 3 ], and SSBP1, involved in p53 transcriptional activity [ 4 ], are up- and down-regulated, respectively, in melanoma cells and that their modulation is involved in melanoma transformation [ 5 ]. It has also been reported that the mutation rate in melanoma is higher than in other solid malignancies.…”
Section: Introductionmentioning
confidence: 99%